Peran Literasi Digital Dan Lingkungan Kerja Terhadap Perilaku Kerja Inovatif Pada Badan Pusat Statistik Kabupaten Mamuju - Aqil, Muhammad; Halim, Agus; Avifa, Zumrotul; Sudirman, Sudirman; Ezra (Journal of Management Branding, 2025)
The purpose of this study is to determine how innovative work practices at the Statistics Indonesia (BPS) office in Mamuju Regency are influenced by digital literacy and the work environment. Multiple linear regression was used for data analysis in this study, which used a quantitative research methodology using a questionnaire for data collection and assessment of the validity and reliability of the research instrument. Partial tests (t-tests) and simultaneous tests (F-tests) were both used in hypothesis testing. The findings of this study indicate that, to some extent, digital literacy contributes positively and significantly to creative work practices. Innovative work behavior is positively and significantly influenced by the workplace. At Statistics Indonesia Mamuju Regency, both digital literacy and the work environment have a significant impact on creative work practices